Extra Corporeal Membrane Oxygenation: A Lifesaving Technology - KC, Tulza (Journal of Nursing Education of Nepal, 2023)
Extracorporeal membrane oxygenation (ECMO) is a mechanical circulatory support device that is used when the heart and/or lung functions are affected by severe disease or organ dysfunction. ECMO therapy provides temporary, lifesaving support to the body until surgical intervention or more permanent treatments can be provided. It may be instituted in a variety of health care settings, from the emergency room to the operating room. It has proven efficacy and is an accepted modality of care for respiratory or cardiopulmonary failure in pediatric and adult populations. Most commonly, it is instituted in an emergency or urgent situation after failure of other treatment modalities. The technology is available in few tertiary level hospitals in Kathmandu. The aim of the review is to share the lifesaving technological interventions carried out in health care settings. Nurses with specialized training are required with ratio of 1:1 or 1:2 for quality vigilant care. Keywords: Extracorporeal membrane, Oxygenation, Extracorporeal life support